P1 ATRIAL TACHYCARDIA IN PATIENT WITH TRANSFUSION–DEPENDENT BETA THALASSEMIA AND SEVERE HEMOCHROMATOSIS: A CASE REPORT. (18th May 2022) - Marchini, F; Sirugo, P; Clò, S; Capanni, A; Malagù, M; Bertini, M; Guardigli, G
Abstract: Background: Beta thalassemia is the most common inherited disease and it's characterized by the reduced synthesis of the beta–globin chains of the hemoglobin. Patients usually need long life transfusions since the disease leads to chronic hemolytic anemia. Iron chelation therapy is essential to prevent the chronic iron overload, which is responsible for heart failure, supraventricular and ventricular arrhythmias up to sudden cardiac death. Case Report: A 31 year old female patient suffering from transfusion–dependent beta thalassemia has rarely taken iron chelation therapy during the years. Because of that, she developed a severe iron overload and heart failure. Furthermore, she started suffering from several episodes of supraventricular tachycardia and she was referred to our cardiological institution for medical help. She was initially treated with a pharmacological rhythm control strategy, which was ineffective. Then, even if the cardiac iron overload wasn't completely resolved, we decided to perform an electrophysiological study and catheter ablation of atrial tachycardia. After the ablation, the patient had no more relapses during the follow up and she started to be more adherent with the iron chelation therapy. Discussion: Cardiovascular complications are among the main causes of morbidity and mortality in patients suffering from beta thalassemia. Despite the wide use of iron–chelation therapy, today it's still possible to find patients with severe iron overload. Furthermore, thalassemic patients have a high arrhythmic burden, especially for supraventricular arrhythmias. The best rhythm control treatment is represented by iron chelation therapy but there are still many doubts and open questions about the optimal pharmacological and interventional strategy. This clinical case shows how the interventional approach with catheter ablation can be an useful tool for rhythm control during the acute phase, even when the cardiac iron overload is still present.